Integrating thermoelectric devices in pyrolysis reactors for biochar and electricity co-production - Soumei Baba; Kazuki Imasato; Atsushi Yamamoto; Takao Ishida; Michihiro Ohta (Energy Conversion and Management: X)
This study proposed an innovative approach to integrating thermoelectric devices with small-scale pyrolysis reactors by using Mizunara (Japanese oak) as the feedstock for biochar production. The primary objective of the study was to enhance the energy efficiency and carbon sequestration potential of the biochar production process by converting waste heat into electricity through thermoelectric devices. Comprehensive steady-state thermal balance analysis revealed that although covering the entire reactor surface with thermoelectric devices can result in excessive heat loss and reduced biochar yield, strategically limiting the installation area allows efficient power generation without considerably compromising biochar production. This balance between electricity generation and biochar yield is critical for optimizing the system’s efficiency. Historically, small-scale waste-heat power generation has been underdeveloped, but our studies have demonstrated that incorporating naturally cooled thermoelectric devices allows the generation of kilowatt-hour (kWh)-scale electricity from waste heat, which would otherwise be discarded. Furthermore, the analysis revealed that with optimized conditions, the CO2 equivalent values of the sequestered carbon can be substantially increased, providing a viable solution for long-term carbon storage. The results highlight the potential of this integrated approach to improve the energy efficiency of biochar production and provide a solution for waste-heat management. Moreover, we assessed the implementation effects by assigning reasonable values for the thermoelectric device performance and provide a robust framework for biomass utilization, waste-heat recovery, and CO2 sequestration.